How Different Training Types and Computer Anxiety Influence Performance and Experiences in Virtual Reality - Eugy Han; Ian Strate; Kristine L. Nowak; Jeremy N. Bailenson (Media and Communication)
Virtual reality (VR) can place people in unique environments and facilitate engagement, making it a compelling tool for storytelling and learning. However, experiencing narratives requires immersion, which can be difficult for those who are anxious about technology. Prior research has shown that training new users on how to use VR before they engage in learning tasks housed in VR is critical. The right kind of training and targeted guidance may help people, including those with computer anxiety, better navigate virtual experiences. However, best practices for how training should be administered remain unclear. This study examined how training type (paper, video, and VR) and computer anxiety influenced outcomes using a large sample size (n = 284). We measured performance and self-reported outcomes while participants navigated computer-graphic scenes, manipulated three-dimensional objects, and watched a narrative 360° video. Results showed that participants who received training via video or VR mastered more VR functions than those who received training via paper. Additionally, those who trained directly in VR had less of a negative experience using VR for completing tasks. Furthermore, participants who trained in VR perceived the training as more useful and found the VR tasks to be easier compared to those who received training in paper or video. Finally, those with high levels of computer anxiety, regardless of training, had more negative outcomes than those with low computer anxiety, including having less mastery of VR functions and engagement with the 360° video content, perceiving the training as being less useful, completing tasks with more difficulty, and having more of a negative experience. Our results suggest that keeping the medium the same both during training and doing is ideal. We discuss implications for theories of information processing in VR, as well as implications for scaled engagement with narratives and learning in VR.